ANALISIS PENYUSUNAN ANGGARAN LABA RUGI DAN METODE PENYUSUNANNYA DALAM PERENCANAAN KEUANGAN PERUSAHAAN - Siti Reskiyawati Said (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2026)
Profit and loss budgeting plays an important role in supporting financial planning, control, and performance evaluation within a company. In an increasingly competitive business environment, organizations are required to manage resources effectively and establish realistic profit targets to ensure financial sustainability. However, many companies still face challenges in preparing profit-oriented budgets that can support managerial decision-making and operational efficiency. Therefore, this study aims to analyze the concept, objectives, roles, and preparation methods of profit and loss budgets in corporate financial management. This study employs a library research method using a descriptive qualitative approach. Data were collected from books, scientific journals, and other academic references related to budgeting and financial management published between 2021 and 2025. The collected data were analyzed through identification, classification, comparison, and interpretation of relevant literature. The results indicate that profit and loss budgeting serves as a strategic tool for planning, controlling, and evaluating corporate financial performance. The preparation of a profit and loss budget requires the integration of various supporting budgets, including sales budgets, production budgets, production cost budgets, operating expense budgets, and tax information. Furthermore, the application of appropriate budgeting methods can assist management in achieving profit targets, improving resource allocation, reducing financial risks, and enhancing organizational effectiveness. In conclusion, the profit and loss budget is not only a financial planning instrument but also an essential management tool that supports decision-making processes and contributes to the achievement of corporate objectives and long-term business sustainability.